Successful treatment of pan-drug resistant Acinetobacter baumannii meningitis/ventriculitis following craniotomy and external ventricular drainage: a case report - Gavrilovska Dimovska, Aleksandra; Veljanovski Hristijan; Jovchevski, Radomir (Oxford University Press and JSCR Publishing Ltd., 2024)
Healthcare-associated central nervous system infections are a significant complication for patients undergoing neurosurgical interventions. We present a case of a 6-year-old patient with an embryonal tumor of the central nervous system. Following a craniotomy for the resection of the tumor, an external ventricular drainage was placed. Several weeks after surgery, she developed signs of meningism. Cerebrospinal fluid cultures were positive for pan-drug resistant Acinetobacter baumannii. Several revisions with the insertion of new external valves were done. She was treated with intravenously meropenem and vancomycin combined with colistin administrated intraventricularly. Significant improvement was seen clinically with negative cultures after 2 weeks. The synergistic action of colistin administrated locally combined with systemic antibiotics may be a promising option for critically ill patients with pan-drug resistant A. baumannii central nervous system infection.
Keywords: central nervous system infection; colistin; intraventricular